COMPARATIVE ANALYSIS OF TRADING VOLUME ACTIVITY (TVA) AND ABNORMAL RETURN (AR) BEFORE AND AFTER IMPLEMENTATION OF TAX AMNESTY POLICY (CASE STUDY ON PROPERTY SECTOR COMPANIES REGISTERED IN JAKARTA ISLAMIC INDEX) - Ragil Aprianti Nur Hidayah; Fajar Adhitya (Universitas Ngudi Waluyo, 2021)
As one of the financial instruments, the development of capital markets could not regardless of the various influences of the environment that includes both economic factors that originate from internal and external companies. One of the Government's policy in 2016 which is quite a concern of investors is the publication of the regulation of the Minister of Finance (FMD) about a Tax Amnesty in Indonesia. To see how big the capital market's reaction against the policy of tax amnesty at the time before and after implementing the policy, then the research will test whether tax policy is the abnormal return can give amnety and improvement trading volume of activity towards the property sector companies listed in Jakarta Islamic Index. These studies use quantitative methods with the event study approach. The population in this study i.e. the property sector companies listed in Jakarta Islamic Index. Determination of purposive sampling technique using samples with specific criteria that result in 4 samples of research. The observation period is 9 months before and after 9 months the implementation of the policy of tax amnesty. Data analysis using the test of normality test and Paired Sample T-Test. Results of the research indicates that there is no significant difference against Trading Volume Activity (TVA) before and after the application of a tax amnesty policy with a value the significance of 0.645 > 0.05. While there is a significant difference against Abnormal Return (AR) between the period before and after the application of a tax amnesty policy with the value significance of 0.001 < 0.05. In other words, a hypothesis first (Ha1) rejected, whereas (Ha2) accepted.